2020
DOI: 10.3168/jds.2019-16855
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters and breeding values for feed intake and energy balance using pedigree relationships or single-step genomic evaluation in Holstein Friesian cows

Abstract: At the beginning of lactation, high-performing dairy cows often experience a severe energy deficit, which in turn is associated with metabolic stress. Increasing feed intake (FI) or reducing the energy deficit during this period could improve the metabolic stability and thus the health of the animals. Genomic selection for the first time enables the inclusion of this hard-to-measure trait in breeding programs. The objective of the current study was the estimation of genetic parameters and genomic breeding valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…These correlations suggest that the resilience indicators are partly determined by different genes in early lactation than in the rest of the lactation. It is commonly observed that traits in early lactation are different than the rest of lactation, such as fat and protein yield (Jamrozik and Schaeffer, 1997), liability to clinical mastitis Heringstad et al, 2004;Negussie et al, 2008), SCC and SCS (Haile-Mariam et al, 2001;Mrode and Swanson, 2003;Elsaid et al, 2011), liability to hoof problems (Alkhoder et al, 2010;Gernand et al, 2013), and traits related to energy balance (Koenen and Veerkamp, 1998;Manzanilla Pech et al, 2014;Harder et al, 2020).…”
Section: Genetic Change Of the Resilience Indicators Within Lactationmentioning
confidence: 99%
“…These correlations suggest that the resilience indicators are partly determined by different genes in early lactation than in the rest of the lactation. It is commonly observed that traits in early lactation are different than the rest of lactation, such as fat and protein yield (Jamrozik and Schaeffer, 1997), liability to clinical mastitis Heringstad et al, 2004;Negussie et al, 2008), SCC and SCS (Haile-Mariam et al, 2001;Mrode and Swanson, 2003;Elsaid et al, 2011), liability to hoof problems (Alkhoder et al, 2010;Gernand et al, 2013), and traits related to energy balance (Koenen and Veerkamp, 1998;Manzanilla Pech et al, 2014;Harder et al, 2020).…”
Section: Genetic Change Of the Resilience Indicators Within Lactationmentioning
confidence: 99%
“…In terms of efficiency, we want to note that DMI in early lactation is genetically low correlated with DMI in late lactation. Different genes affect DMI at different lactation stages (Berry et al, 2007;Tetens et al, 2014;Harder et al, 2020). Spurlock et al (2012) concluded this for EB as well.…”
Section: Discussionmentioning
confidence: 80%
“…Any deviations from these standards can negatively affect milk production [7][8][9]. Dairy cattle breeding has long been aimed at a high milk yield, often at the expense of functional traits, the loss of which may entail health disorders and affect longevity [10][11][12][13][14][15]. Animals with high genetic resistance maintain a good production level despite the frequently negative impact of exogenous factors [16,17].…”
Section: Introductionmentioning
confidence: 99%